IS KNOWLEDGE OF DIABETES MELLITUS A PREREQUISITE FOR OPTIMAL SELF-CARE AND CONTROL OF THIS DISEASE? - Jandrić-Kočić, Marijana (HEALTH CARE, 2025)
Diabetes mellitus (DM) is the most common endocrinological disease of the modern era of pandemic proportions. People with DM have an increased risk of premature death caused by cardiovascular and other diseases compared to the general population. Patients’ knowledge about DM includes a series of beliefs about different aspects of the disease that patients have accumulated during their lifetime, before and after diagnosis. This knowledge represents a significant cognitive factor that can influence a person’s adaptation to the disease, the course of the disease and its treatment. In this review, it was examined whether knowledge about DM is a prerequisite for optimal self-care and control of this disease. The literature search was conducted using the following key words: diabetes mellitus, self-management, knowledge and education in PubMed, Emabase, Scopus, SCIndex and Hrčak for the period from 2001 to 2024. The largest number of studies on DM patients’ knowledge used the Diabetes Knowledge Questionnaire (DKQ) with 24 items. In patients with DM type 1 and DM type 2 who participated in these studies, ubiquitous, deficient knowledge about DM was observed, which the authors link to suboptimal blood glucose values, high morbidity and mortality of the patients. Family history of DM, younger age and college education were independent predictors of optimal knowledge of patients with DM in most studies. Routine assessment of the level of knowledge of patients with DM through standardized questionnaires, accompanying identification of vulnerable groups and their education would enable the improvement of the knowledge of patients and the acquisition of skills necessary for self-menagement.